O18-5 Occupational exposure to diesel exhaust and alterations in immune/inflammatory markers. (1st September 2016) - Lan, Qing; Bassig, Bryan A; Vermeulen, Roel; Dai, Yufei; Ren, Dianzhi; Hu, Wei; Duan, Huawei; Niu, Yong; Xu, Jun; Shiels, Meredith; Kemp, Troy J; Fu, Wei; et al.
Abstract : Introduction: Diesel engine exhaust (DEE) is a known lung carcinogen in humans (IARC Group 1). However, the biological mechanism underlying this association is unclear. Given the suspected relationship between inflammation and lung carcinogenesis, we evaluated associations between DEE exposure and a multiplex panel of immune markers in workers exposed to DEE and unexposed workers in China. Methods: A cross-sectional molecular epidemiology study was conducted among 54 workers exposed to DEE in a diesel engine testing facility, and 55 unexposed workers who were employed in separate factories. Repeated personal exposure measurements of elemental carbon (EC) were taken from workers before blood collection. Serum levels of immune markers were analysed using a Luminex bead-based assay. Linear regression was used to evaluate differences in marker concentrations between DEE exposed vs. unexposed workers, and to explore exposure-response trends with EC. Results: Four markers were significantly associated with DEE exposure in analyses of exposed vs. unexposed workers (P-value < 0.05). Significant monotonic trends in relation to increasing EC levels were observed for CXCL-11/I-TAC (19% reduction in exposed workers overall) and CCL15/MIP-1D (21% increase in exposed workers overall). Analyses of DEE exposed vs. unexposed workers stratified by smoking status found that an additional marker (CCL2/MCP-1) was significantly increased in workers exposed to DEE among never and former smokers, but not current smokers (Pinteraction = 0.01). Conclusions: Recent evidence suggests that higher levels of CCL15/MIP-1D and CCL2/MCP-1, two markers in the CC chemokine subfamily that attract white blood cells to sites of inflammation, are associated with increased risk of lung cancer in Asian never-smoking women. Alterations in these markers in the same direction among workers exposed to DEE in our study may provide mechanistic insight into the relationship between DEE and lung carcinogenesis.